PEMAHAMAN TENTANG PENGELOLAAN SAMPAH PLASTIK PADA SISWA KELAS 6 SDN 4 JEROWARU - Paryono, Paryono; Diniariwisan, Damai; Hilyana, Sitti; Amir, Sadikin; Himawan, Mahardika R.; Maylanda, Donna A.; Ardiansyah, Ardiansyah; Rahman, Ibadur; Lestariningsih, Wiwid Andriyani; Jefri, Edwin; Nurliah, Nurliah; Larasati, Chandrika Eka; et al. (Jurnal Pepadu, 2023)
Plastic waste is a type of inorganic waste that poses a serious threat to the environment because in addition to increasing amount, plastic is also difficult to decompose by natural processes. Education about plastic waste management need to be done as early as possible. The purpose is to find out and increase students' understanding of SDN 04 Jerowaru about plastic waste management. This community service activity method uses an approach through filling out a questionnaire, discussion, pratice to find out the extent of students' understanding of waste and its management. Student knowledge based on the results of questionnaires and questions and answers about the definition of waste and types of waste. Most of the students already have good knowledge. However, there are still students who have not answered correctly about the impact of plastic waste where the percentage is still above 40%, which means that there are still quite a number of students who do not know well the dangers that can arise from plastic waste. An understanding of management is one of the first steps to increase student awareness so they want to reduce plastic use.